2006
DOI: 10.1159/000093213
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Deep Brain Stimulation of the Subthalamic Nucleus for Parkinson’s Disease: Effects on Cognition, Mood, Anxiety and Personality Traits

Abstract: Objective: To evaluate modifications occurring in cognitive functions and behavioural aspects in a group of 72 consecutive patients with Parkinson’s disease (PD) 15 months after bilateral deep brain stimulation (DBS) of the subthalamic nucleus (STN). Methods: 72 consecutive PD patients bilaterally implanted for DBS of the STN were evaluated before and after surgery with a mean follow-up of 15 months. A neuropsychological assessment was performed to evaluate reasoning (Raven Colour Matrices), memory (Bisyllabic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(143 citation statements)
references
References 76 publications
6
132
0
5
Order By: Relevance
“…Both STN-and GPi-DBS can have non-motor side effects, especially affecting verbal fluency, cognition and mood (Kumar et al, 1999a, b;Dujardin et al, 2001;Schupbach et al, 2005;Smeding et al, 2005Smeding et al, , 2006Smeding et al, , 2011Castelli et al, 2006;De Gaspari et al, 2006, Merello et al, 2008. Verbal fluency and cognition problems are more often seen in old patients (Hariz et al, 2000;Saint-Cyr et al, 2000;Funkiewiez et al, 2004;Smeding et al, 2011), or in those with poor cognition or depression at baseline (De Gaspari et al, 2006).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both STN-and GPi-DBS can have non-motor side effects, especially affecting verbal fluency, cognition and mood (Kumar et al, 1999a, b;Dujardin et al, 2001;Schupbach et al, 2005;Smeding et al, 2005Smeding et al, , 2006Smeding et al, , 2011Castelli et al, 2006;De Gaspari et al, 2006, Merello et al, 2008. Verbal fluency and cognition problems are more often seen in old patients (Hariz et al, 2000;Saint-Cyr et al, 2000;Funkiewiez et al, 2004;Smeding et al, 2011), or in those with poor cognition or depression at baseline (De Gaspari et al, 2006).…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
“…Even when present, the impact of changes in verbal fluency on the quality of life appears to be relatively small (Alegret et al, 2004;Morrison et al, 2004;Montel and Bungener, 2009;Zahodne et al, 2009). Although almost half patients with DBS experience variable degrees of cognitive changes (Higginson et al, 2009), these deficits become 'relevant' in less than 10% treated patients (Castelli et al, 2006;Tir et al, 2007). However, because DBS is now widely used, even for patients with early PD in some centers, these adverse effects remain a major concern.…”
Section: Non-motor Side Effects Of Stn and Gpi-dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that DBS suppresses motor symptoms and reduces the total dose of the antiparkinsonian drugs 2,3 . Among the adverse effects of STN-DBS in patients with PD, the postoperative decline in verbal fluency is well documented 4,5,6,7,8,9,10,11 . However, there are fewer studies about the effect of the stimulation per se, comparing on-and off-stimulation conditions 12,13,14 .…”
Section: Subthalamic Nucleus Deep Brain Stimulation (Stn-dbs)mentioning
confidence: 99%
“…Also, the majority of previous studies pointed to a negative effect of STN-DBS on verbal fluency when they studied postsurgical patients 22 . Some of the studies on pre-and post-DBS have found a decline in phonemic fluency 5,7,10 , others a decline in semantic fluency 6 and still others in both verbal fluency tasks 4,8,9 .…”
Section: Variable M (Sd) or N (%)mentioning
confidence: 99%